The Correlation between covid-19 infection and inflammatory biomarkers in hospitalized patients - Abdalwahab B. Hussain; Abdullah A. Saud; Abdulrahman I. Allawy; Rawaa A. Muhammed (مجلة مركز بحوث التقنيات الاحيائية, 2022)
Pulmonary inflammation during COVID-19 that cause tissue destruction along with coagulopathy and heamatological dysregulation were noticed among many patients which are overlapping and did not elucidate a specific pattern among those patients, therefore; our study was case control study conducted on 150 inpatients in Fallujah Teaching Hospital and 50 healthy control from January to September 2021, our study aimed to study the haematological markers including haemoglobin, leukocyte with differential count and platelets, along with studying inflammatory biomarkers consisting of C-reactive protein, Erythrocyte sedimentation rate, Lactate dehydrogenase, ferritin and D-dimer. Most of haematological, inflammatory and coagulation markers were high in patient group compared with control healthy group significantly. Elderly are more prone to highly elevated ESR compared with younger ages significantly. Despite the high count of WBC, neutrophils and lymphocytes represent lower values in patients compared with control which exacerbated with increasing of age especially in lymphocytes. The study concluded poor outcome in hospitalized patients with high destruction and inflammatory response. Ferritin elevation noticed in patients compared with control caused by highly inflammatory response. elderly would be more prone to secondary bacterial and viral infections due to decreased immunological response represented with lower counts of lymphocyte compared with healthy group.